Shifting paradigms in Europe's approach to cyber defence: Ambitions to disrupt malicious cyber activity need to protect norms as well as networks - Annegret Bendiek; Jakob Bund (Stiftung Wissenschaft und Politik (SWP), 2023)
As high-level European Union (EU) policy documents call for investment in active cyber defence capabilities, the legal and political powers for their use remain ill-defined. To demonstrate their commitment to principles of responsible state behaviour and due diligence, the EU and its member states have a duty to establish the normative foundations for the use of active cyber defence measures ahead of their deployment, while carefully managing the risk of a gradual militarisation of the cyber and information domain.
Keywords: 320; cyber defence; cyberattacks; cyber power; ransomware; hackback; Due Diligence; Botnets; Defend Forward; US Cyber Command; Paul Nakasone; Hunt Forward Operation (HFO); EU Cyber Rapid Response Teams; CRRT; EUCDCC; Sovereign Cyber Effects Provided Voluntarily by Allies; SCEPVA; Permanent Structured Cooperation (PESCO); European Union (EU)